Thirty-day unplanned readmission in hospitalised asthma patients in the USA. Issue 1165 (30th September 2021) - Patel, Neel; Singh, Sandeep; Desai, Rupak; Desai, Aakash; Nabeel, Mohammed; Parikh, Neil; Singh, Gagandeep; Patel, Smit; Parikh, Radhika; Mahajan, Supriya
Abstract: Introduction: Hospital quality improvement and hospital performance are commonly evaluated using parameters such as average length of stay (LOS), patient safety measures and rates of hospital readmission. Thirty-day readmission (30-DR) rates are widely used as a quality indicator and a quantifiable metric for hospitals since patients are often readmitted for the exacerbation of conditions from index admission. The quality of patient education and postdischarge care can influence readmission rates. We report the 30-DR rates of patients with asthma using a national dataset for the year 2013. Objectives: The aim of our study was to assess the 30- day readmission (30-DR) rate as well as, the causes and predictors of readmissions. Study designs/methods: Using the Nationwide Readmission Database (NRD) (2013), we identified primary discharge diagnoses of asthma by using International Classification of Diseases, Ninth Revision, Clinical Modification code '493'. Categorical and continuous variables were assessed by a χ 2 test and a Student's t-test, respectively. The independent predictors of unplanned 30-DR were detected by multivariate analysis. We used sampling weights, which are provided in the NRD, to generate the national estimates. Results: There were 130 490 (weighted N=311 173) inpatient asthma admissions during 2013. The overall 30-DR for asthma was 11.9%. The associated factors for 30-DR were age 45–84 years (40.32% vs 29.05%; p<0.001), enrolment in Medicare (49.33% vs 30.61% p<0.001), extended LOS (mean, 4.40±0.06 vs 3.25±0.04 days; p<0.001), higher mean cost (US8593.91 vs US6741.31; p<0.001) and higher disposition against medical advice (DAMA) (4.14% vs 1.51%; p<0.001). The factors that increased the chance of 30-DR were advanced age (≥45–64 vs ≤17 years; OR 4.61, 95% CI 4.04 to 5.27, p<0.0001), male sex (OR 1.19, 95% CI 1.13 to 1.26, p<0.0001), a higher Charlson Comorbidity Index (CCI) (OR 1.16, 95% CI 1.14 to 1.18, p<0.0001), DAMA (OR 2.32, 95% CI 2.08 to 2.59, p<0.0001), non-compliance with medication (OR 1.34, 95% CI 1.24 to 1.46, p<0.0001), post-traumatic stress disorder (OR 1.48, 95% CI 1.22 to 1.79, p<0.0001), alcohol use (OR 1.45, 95% CI 1.27 to 1.65, p<0.0001), gastro-oesophageal reflux disease (OR 1.20, 95% CI 1.14 to 1.27, p<0.0001), obstructive sleep apnoea (OR 1.11, 95% CI 1.03 to 1.18, p<0.0042) and hypertension (OR 1.11, 95% CI 1.06 to 1.17, p<0.0001). Conclusions: We found that the overall 30-DR rate for asthma was 11.9% all-cause readmission. Major causes of 30-DR were asthma exacerbation (36.74%), chronic obstructive pulmonary disease (11.47%), respiratory failure (6.46%), non-specific pneumonia (6.19%), septicaemia (3.61%) and congestive heart failure (3.32%). One-fourth of the revisits occurred in the first week, while half of the revisits took place in the first 2 weeks. Education regarding illness and the importance of medicine compliance could play a significant role in preventing asthma-related readmission.